PENGARUH CO-BRANDING, PERCEIVED VALUE, DAN USER-GENERATED CONTENT TERHADAP PURCHASE INTENTION PRODUK KOLABORASI MCDONALD'S X NEW JEANS - Marsya Adelia Avianti Irawan (2023)
The high competition among fast food restaurants in Indonesia requires companies to implement effective marketing strategies. Currently, there is a strategy that is often used by companies, namely co-branding, such as co-branding between McDonald's and New Jeans. The occurrence of this phenomenon along with perceived value and user-generated content that affects purchase intention for products resulting from the McDonald's x New Jeans collaboration results in the formulation of problems related to whether co-branding, perceived value, and user-generated content can affect purchase intention. This study was conducted with the aim of proving whether co-branding, perceived value, and user-generated content can influence purchase intention. The population in this study were McDonald's consumers who knew the McDonald's x New Jeans product in DKI Jakarta with a sample of 100 respondents using non-probability sampling and purposive sampling. This research uses quantitative methods with Smart PLS 4.0. The results of this study indicate that the variables of co-branding, perceived value, and user-generated content have a positive and significant influence on the purchase intention of McDonald's x New Jeans collaboration products.